Physical activity and quality of life in the group of women participating in senior education - Jurkiewicz, Beata; Barnaś, Edyta; Kołpa, Małgorzata (Journal of Education, Health and Sport, 2022)
Introduction. Maintaining mobility and extending the period of functional activity in everyday life is the basis for gerontological prevention for the elderly. An important task in the physical culture strategy for an aging society is to prepare both oneself and one’s family for old age (education "in old age" and "towards old age"). Educational institutions for activation of seniors play a very important role in this area. The aim of the study was to analyze the relationship between physical activity and quality of life of women 65+, including participation in senior education. Material and methods. The study was conducted among inhabitants of Tarnów province (southern Poland) aged 65+: 205 educationally active seniors (group I) and 207 women who do not benefit from senior education (group II). The diagnostic survey method and standardized interview technique using the WHOQoL-AGE quality of life questionnaire were used. The level of significance was adopted as p≤0.05. Results and conclusions. Educationally active seniors significantly more often declared systematic physical activity. Regular physical activity was most often undertaken by women in the youngest age group. It is recommended to carry out activities promoting participation in various forms of physical activity, especially in the two oldest age groups (old & oldest old). It is also proposed to continue research on the quality of life and its determinants by gender, and the results of these studies can be used by managers and decision-makers in the local health care sector to develop health-promoting strategies targeted at specific groups.